Solid-State Nuclear Magnetic Resonance as a Tool to Probe the Impact of Mechanical Preprocessing on the Structure and Arrangement of Plant Cell Wall Polymers - Munson, Coyla R.; Gao, Yu; Mortimer, Jenny C.; Murray, Dylan T. (Frontiers in Plant Science, 2022)
Efficient separation of the plant cell wall polymers during lignocellulose processing has been historically challenging due to insolubility of the polymers and their propensity for recalcitrant reassembly. Methods such as lignin first extraction techniques have advanced efficient biomass use, but recalcitrance remains. Issues include the initial physical processing steps required for reducing particle size and solubilizing the plant cell wall, prior to depolymerization. Here, we discuss how solid-state Nuclear Magnetic Resonance (NMR) approaches are illustrating how even minimal physical processing can disrupt the 3D organization of cellulose, xylan, and lignin. The organization of these polymers in the secondary plant cell walls varies across biomass sources and sample preparation methods. These structural differences will contribute to variable efficiencies for biofuels and bioproducts downstream processing. We propose that these methods can be applied to follow biomass deconstruction, and understand polymer rearrangements that can lead to poor yields. The utility of the technique is illustrated using the vibratory ball milling of Sorghum bicolor as an example.